Reﬂections of a Mi’kmaq social worker on a quarter of a century work in First Nations child welfare - MacDonald, Nancy; MacDonald, Judy (First Peoples Child & Family Review, 2007)
First Nations people would argue that the ‘Sixties Scoop’ of removing their children from their homes and culture never ended. First Nations children entering ‘care’ of child welfare agencies has increased signiﬁcantly since the 1960s and 1970s. Storying the journey of a Mi’kmaq social worker working with a First Nations child, aspects of the child welfare system will be theoretically and historically located and critiqued from a social justice perspective. Schools of Social Work will be challenged to provide an education inclusive of decolonization, understanding the historical limitations of the child welfare system and its impact upon First Nations peoples.